Identification of Quantity Surveyor Competency Risk for Cost Overrun - Pondaag, Reynard; Latief, Yusuf (Devotion : Journal of Research and Community Service, 2023)
Appropriateness of costs in the process of building a high-rise building is one of the success criteria for a construction project. However, the main problem that is often faced by most construction projects is related to the occurrence of cost overruns. Quantity Surveyor has an important role in a construction project. According to IQSI, the role of the Quantity Surveyor consists of 4 main scopes, namely planning and controlling construction costs, documenting the completeness of tender documents, contract administration, and arbitration. This study aims to identify risk factors and risk ratings from the competency of the Quantity Surveyor that have the potential to cause cost overruns. The method used in this study is the Delphi method, to validate the risks obtained from the literature study. From the results of the analysis, 52 variables with a moderate level of risk were obtained, and 3 variables with a high level of risk in the pre-construction and construction stages which could cause cost overruns.